An ED paradox: patients who arrive by ambulance and then leave without consulting an ED provider. Issue 3 (4th October 2016) - Doupe, Malcolm B; Day, Suzanne; Palatnick, Wes; Chochinov, Alecs; Chateau, Dan; Snider, Carolyn; Lobato de Faria, Ricardo; Weldon, Erin; Derksen, Shelley
Abstract : Background: Scientists have called for strategies to identify ED patients with unmet needs. We identify the unique profile of ED patients who arrive by ambulance and subsequently leave without consulting a provider (ie, a paradoxical visit, PV). Methods: Using a retrospective cohort design, administrative data from Winnipeg, Manitoba were interrogated to identify all ED patients 17+ years old as having zero, single or multiple PVs in 2012/2013. Analyses compare the sociodemographic, physical (eg, arthritis), mental (eg, substance abuse) and concurrent healthcare use profile of non-PV, single and multiple PV patients. Results: The study cohort consisted of 122 639 patients with 250 754 ED visits. Across all ED sites, 2.3% of patients (N=2815) made 3387 PVs, comprising 1.4% of all ED visits. Descriptively, more single versus non-PV patients lived in urban core and lowest-income areas, were frequent ED users generally, were substance abusers and had seven plus primary care physician visits. Multiple PV patients had a similar but more extreme profile versus their single PV counterparts (eg, 54.7% of multiple vs 27.4% of single PV patients had substance abuse challenges). From multivariate statistics, single versus non-PV patients are defined uniquely by their frequent ED use, by their substance abuse, as living in a core and low income area, and as having multiple visits with primary care physicians. Conclusions: PV patients have needs that do not align with the acute model of ED care. These patients may benefit from a more integrated care approach likely involving allied health professionals.